2017
DOI: 10.1371/journal.pone.0188464
|View full text |Cite
|
Sign up to set email alerts
|

Osteoglycin inhibition by microRNA miR-155 impairs myogenesis

Abstract: Skeletal myogenesis is a regulated process in which mononucleated cells, the myoblasts, undergo proliferation and differentiation. Upon differentiation, the cells align with each other, and subsequently fuse to form terminally differentiated multinucleated myotubes. Previous reports have identified the protein osteoglycin (Ogn) as an important component of the skeletal muscle secretome, which is expressed differentially during muscle development. However, the posttranscriptional regulation of Ogn by microRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…miR-155 impairs myogenesis 31 , 32 ; moreover, its targets TSPAN13 and LRP1B are also targeted by miR-222 and miR-381, respectively, suggesting a potential cooperative action between these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 impairs myogenesis 31 , 32 ; moreover, its targets TSPAN13 and LRP1B are also targeted by miR-222 and miR-381, respectively, suggesting a potential cooperative action between these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…3c). Since miR-155 can inhibit myoblast differentiation and skeletal muscle formation [10, 11], whether the low expression of miR-155 is related to the rapid growth of broilers needs to be further studied in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the emerging evidences of miR-155 role in the development of skeletal muscle and adipogenesis have been noticed recently. On the one hand, miR-155 can repress the expression of MEF2A (a member of the myogenic enhancer factor 2 family of transcription factors) and osteoglycin (Ogn, an important component of the skeletal muscle secretome), and inhibit proliferation and differentiation of myoblast cells [10, 11]. Moreover, miR-155 also regulates the expression of Olfactomedin-like 3 (OLFML3), which may affect prenatal skeletal muscle development in pig [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our transcriptome data from C2C12 muscle cells treated with TNF-α/IFN-γ further support this fact by presenting not only a reduction in the expression of collagen genes but also in other genes involved in ECM assembly, including Ogn. Our group had previously shown that Ogn affects the proliferation and differentiation of C2C12 muscle cells [85]. A previous study has also investigated the potential contributory factors outside the fiber within the muscle microenvironment in humans and animals and found that Pax7 responds to NF-κB by impairing the regenerative capacity of myogenic cells to drive muscle wasting in cancer cachexia [80].…”
Section: Discussionmentioning
confidence: 98%